Intergenerational Transmission of Reflective Functioning - Rosso, Anna M.; Airaldi, Cinzia (Frontiers in Psychology, 2016)
The present study investigated whether, and to what extent, reflective functioning (RF) during preadolescence is associated with maternal attachment security and reflective functioning, and with the child’s attachment security. Thirty-nine mother-preadolescent child dyads from a non clinical population participated in the study. Maternal and child RF were assessed by applying the Reflective Functioning Scale (RFS) to the Adult Attachment Interview (AAI) and to the Child Attachment Interview (CAI) transcripts. Children of mothers who showed a secure attachment model regarding the relationship with their parents during childhood reported higher levels of RF than the children of mothers who were classified as insecure on the AAI. Child RF was positively associated with maternal “Coherence of the Mind” on the AAI and negatively associated with maternal derogation of attachment. A strong, significant association was also found between child attachment security and child reflective functioning. Children who were rated as being more emotionally open, more able to balance positive and negative descriptions of their parents, more prone to support their assertions through examples, and more able to positively resolve conflicts with their parents showed higher reflective functioning. On the contrary, children who resorted to a higher extent to idealization and dismissal towards their parents showed a lesser degree of reflective functioning. Notably, a very strong association was found between the score on the “Overall coherence” subscale and the child’s ability to mentalise mixed-ambivalent mental states in the context of their family relationships. As expected, child and maternal reflective functioning resulted significantly positively correlated with each other. In particular, only maternal reflective functioning (and not maternal attachment security) predicted child reflective functioning, and only maternal ability to mentalise mixed-ambivalent mental states predicted the corresponding ability in the children.